Comparative Transcriptomics of Shiga Toxin-Producing and Commensal Escherichia coli and Cytokine Responses in Colonic Epithelial Cell Culture Infections - Harrison, Lisa M.; Lacher, David W.; Mammel, Mark K.; Leonard, Susan R. (Frontiers in Cellular and Infection Microbiology, 2020)
Ingestion of Shiga toxin-producing Escherichia coli (STEC) can result in a range of illness severity from asymptomatic to hemorrhagic colitis and death; thus risk assessment of STEC strains for human pathogenicity is important in the area of food safety. Illness severity depends in part on the combination of virulence genes carried in the genome, which can vary between strains even of identical serotype. To better understand how core genes are regulated differently among strains and to identify possible novel STEC virulence gene candidates that could be added to the risk assessment repertoire, we used comparative transcriptomics to investigate global gene expression differences between two STEC strains associated with severe illness and a commensal E. coli strain during in vitro intestinal epithelial cell (IEC) infections. Additionally, we compared a wide array of concomitant cytokine levels produced by the IECs. The cytokine expression levels were examined for a pattern representing STEC pathogenicity; however, while one STEC strain appeared to elicit a proinflammatory response, infection by the other strain produced a pattern comparable to the commensal E. coli. This result may be explained by the significant differences in gene content and expression observed between the STEC strains. RNA-Seq analysis revealed considerable disparity in expression of genes in the arginine and tryptophan biosynthesis/import pathways between the STEC strains and the commensal E. coli strain, highlighting the important role some amino acids play in STEC colonization and survival. Contrasting differential expression patterns were observed for genes involved in respiration among the three strains suggesting that metabolic diversity is a strategy utilized to compete with resident microflora for successful colonization. Similar temporal expression results for known and putative virulence genes were observed in the STEC strains, revealing strategies used for survival prior to and after initial adherence to IECs. Additionally, three genes encoding hypothetical proteins located in mobile genetic elements were, after interrogation of a large set of E. coli genomes, determined to likely represent novel STEC virulence factors.